Clinicopathological and genetic differences between low‐grade and high‐grade colorectal mucinous adenocarcinomas. Issue 24 (21st October 2015) - Yoshioka, Yasumasa; Togashi, Yosuke; Chikugo, Takaaki; Kogita, Akihiro; Taguri, Masataka; Terashima, Masato; Mizukami, Takuro; Hayashi, Hidetoshi; Sakai, Kazuko; de Velasco, Marco A.; Tomida, Shuta; Fujita, Yoshihiko; et al.
Abstract : BACKGROUND: Although colorectal mucinous adenocarcinomas (MCs) are conventionally regarded as exhibiting high‐grade differentiation, they can be divided by differentiation into 2 groups according to the glandular appearance: low‐grade mucinous adenocarcinoma (low‐MC) and high‐grade mucinous adenocarcinoma (high‐MC). METHODS: Patients with colorectal cancer (CRC) who underwent surgical resection between 2000 and 2012 were enrolled in this study. Among the cases with MC, the clinicopathological and genetic differences between low‐MC and high‐MC were investigated with next‐generation sequencing. RESULTS: A total of 1373 patients with CRC were analyzed. Forty patients (2.9%) had MC, and 13 patients had high‐MC. Patients with MC had significantly shorter disease‐free survival (DFS) and overall survival (OS) periods than those with nonmucinous carcinoma. When low‐MC patients and high‐MC patients were compared, those with high‐MC had significantly shorter DFS and OS periods than those with low‐MC. Multivariate analyses revealed that high‐MC was significantly associated with both shorter DFS and shorter OS, but low‐MC was not. A genome analysis revealed that low‐MC had a considerably larger number of mutations than high‐MC, and Kirsten rat sarcoma viral oncogene homolog ( KRAS ) mutations and adenomatous polyposis coli mutations were particularly frequently found in low‐MC. In contrast, SMAD family member 4 ( SMAD4 ) mutations were frequently found in high‐MC. CONCLUSIONS: High‐MC is an independent prognostic factor in CRC (but low‐MC is not), and it is genetically different from other CRCs, including low‐MC. Both the clinicopathological differences and the genetic differences suggest that low‐MC and high‐MC should be distinguished in clinical settings. Cancer 2015;121:4359–68 . © 2015 American Cancer Society . Abstract : The clinicopathological and genetic differences between low‐grade mucinous adenocarcinoma and high‐grade mucinous adenocarcinoma have been investigated with next‐generation sequencing for the first time. High‐grade mucinous adenocarcinoma is an independent prognostic factor in colorectal cancer (but low‐grade mucinous adenocarcinoma is not), and it is genetically different from other colorectal cancers, including low‐grade mucinous adenocarcinoma. These differences suggest that low‐grade mucinous adenocarcinoma and high‐grade mucinous adenocarcinoma should be distinguished in clinical settings.